2018
DOI: 10.21608/puj.2018.16316
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the intestinal immune response in Giardia duodenalis experimentally infected rats using quantitative real-time PCR

Abstract: Background: Giardia duodenalis is a well-known intestinal parasite. The host immune response needs much effort to be clarified. Objective: Evaluation of the transcriptional level of a panel of cytokines in intestinal tissue and assessing the correlation between these levels and cyst count. Material and Methods: An experimental G. duodenalis infection was conducted in a rat model composed of twentyfive laboratory-bred, parasite-free male albino rats, divided into 10 for control group and 15 for infected group. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Muñoz-Cruz et al (2018) reported the TNF-role in the early control of giardiasis, by significantly released by mast cells on infection time. Mahmoud et al (2018) found that peak up-regulation of gene expression of TNF-inal tissue was 7 th dpi. Zhao et al (2022) showed that mRNA levels of TNF--1, & IL-6 transcription and protein expression were significantly higher in giardiasis than controls.…”
Section: Discussionmentioning
confidence: 98%
“…Muñoz-Cruz et al (2018) reported the TNF-role in the early control of giardiasis, by significantly released by mast cells on infection time. Mahmoud et al (2018) found that peak up-regulation of gene expression of TNF-inal tissue was 7 th dpi. Zhao et al (2022) showed that mRNA levels of TNF--1, & IL-6 transcription and protein expression were significantly higher in giardiasis than controls.…”
Section: Discussionmentioning
confidence: 98%
“…However, the mechanisms of host defence used to regulate Giardia infections are not fully understood 8 . The mechanisms of innate immunity involve antimicrobial peptide (AMP) production, nitric oxide (NO), phagocytosis of macrophage, lymphocyte development and dendritic cell (DC) migration to the site of infection 9 . Paneth cells and other cells secrete AMPs that can destroy trophozoites 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, Li et al 12 stated that the immune response induced by Giardia infection in BALB/c mice included that IL‐4, IL‐5 and IL‐10 cytokines as well as IgG and IgE antibodies. IL‐4 is important to boost Th2 and to inhibit Th1 differentiation, and increased IL‐10 synthesis during infection may counterbalance inflammatory responses 9 . As a potent anti‐inflammatory cytokine, IL‐10 has been shown to suppress IFN‐γ‐induced macrophage killing ability against intra‐ and extracellular parasites and to avoid immune‐mediated degradation of the host tissue in reaction to infectious agents 24 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations